IPEM topical report: the first UK survey of dose indices from radiotherapy treatment planning computed tomography scans for adult patients. (10th September 2018) - Wood, Tim J; Davis, Anne T; Earley, James; Edyvean, Sue; Findlay, Una; Lindsay, Rebecca; Nisbet, Andrew; Palmer, Antony L; Plaistow, Rosaleen; Williams, Matthew
Abstract: CT scans are an integral component of modern radiotherapy treatments, enabling the accurate localisation of the treatment target and organs-at-risk, and providing the tissue density information required for the calculation of dose in the treatment planning system. For these reasons, it is important to ensure exposures are optimised to give the required clinical image quality with doses that are as low as reasonably achievable. However, there is little guidance in the literature on dose levels in radiotherapy CT imaging either within the UK or internationally. This IPEM topical report presents the results of the first UK wide survey of dose indices in radiotherapy CT planning scans. Patient dose indices were collected for prostate, gynaecological, breast, lung 3D, lung 4D, brain and head and neck scans. Median values per scanner and examination type were calculated and national dose reference levels and 'achievable levels' of CT dose index (CTDIvol ), dose-length-product (DLP) and scan length are proposed based on the third quartile and median values of these distributions, respectively. A total of 68 radiotherapy CT scanners were included in this audit. The proposed dose reference levels for CTDIvol and DLP are; prostate 16 mGy and 570 mGy · cm, gynaecological 16 mGy and 610 mGy · cm, breast 10 mGy and 390 mGy · cm, lung 3D 14 mGy and 550 mGy · cm, lung 4D 63 mGy and 1750 mGy · cm, brain 50 mGy and 1500 mGy · cm and head and neck 49 mGy and 2150 mGy · cm. Significant variations in dose indices were noted, with head and neck and lung 4D yielding a factor of eighteen difference between the lowest and highest dose scanners. There was also evidence of some clustering in the data by scanner manufacturer, which may be indicative of a lack of local optimisation of individual systems to the clinical task. It is anticipated that providing this data to the UK and wider radiotherapy community will aid the optimisation of treatment planning CT scan protocols.